How to be an adult in relationships : the five keys to mindful loving - Richo, David, 1940- (Shambhala, 2021)
""Most people think of love as a feeling," says David Richo, "but love is not so much a feeling as a way of being present." Drawing on the Buddhist concept of mindfulness, Richo offers a fresh perspective on love and relationships that focuses not on finding an ideal mate but on becoming a more loving and realistic person. Here, he explores five hallmarks of mindful loving and how they play a key role in our relationships throughout life: Attention to the present moment; observing, listening, and noticing all the feelings at play in our relationships Acceptance of ourselves and others just as we are Appreciation of all our gifts, our limits, our longings, and our poignant human predicament Affection shown through holding and touching in respectful ways Allowing life and love to be just as they are, with all their ecstasy and ache, without trying to take control When deeply understood and applied, these five simple concepts-what Richo calls the five A's-form the basis of mature love. They help us to move away from judgment, fear, and blame to a position of openness, compassion, and realism about life and relationships. By giving and receiving these five A's, relationships become deeper and more meaningful, and they become a ground for personal transformation"--